Development of a forensic DNA phenotyping panel using massive parallel sequencing. Issue 1 (December 2019) - Turchi, Chiara; Onofri, Valerio; Melchionda, Filomena; Fattorini, Paolo; Tagliabracci, Adriano
Abstract: The HIrisPlex-S system, targeting a total of 41 SNPs, allows the simultaneous eye, hair and skin color prediction from DNA. In the present study, we developed a massive parallel sequencing (MPS) multiplex assay in order to genotype all the HIrisPlex-S markers in degraded casework samples. PCR amplicons sizes of target regions were kept below 180 bp, in order to allow analysis of degraded DNA samples. Individuals with known phenotype, artificially degraded DNA samples and a set of 2800M control DNA dilutions were sequenced on a Ion PGM System, in order to evaluate the concordance testing results and the forensic suitability of this 41-plex MPS assay. Full and reliable profiles could be obtained with 0.1 ng of input DNA. The increment of the number of PCR cycles results in improvement of sensitivity or in typing results but an increase of artifacts were also observed.